2016
DOI: 10.4037/ajcc2016814
|View full text |Cite
|
Sign up to set email alerts
|

Family Presence During Resuscitation: Impact of Online Learning on Nurses’ Perception and Self-confidence

Abstract: Background Family presence during resuscitation (FPDR) is supported by patients and their family members. Nurses, however, including critical care nurses who frequently implement resuscitative care, have mixed views. Objectives To determine the impact of online learning on critical care nurses’ perception of and self-confidence with FPDR. Methods A 2-group, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…The tools have also been used to assess the effectiveness of educational interventions to increase student nurses knowledge, perception and confidence in facilitated family-witnessed resuscitation (Kantrowitz-Gordon, 2013;Powers, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The tools have also been used to assess the effectiveness of educational interventions to increase student nurses knowledge, perception and confidence in facilitated family-witnessed resuscitation (Kantrowitz-Gordon, 2013;Powers, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the outcomes explored in our review were examined in other studies of e-learning directed at health and social care practitioners, particularly confidence and related selfefficacy. A recent PhD thesis confirmed the positive impact of an e-learning module on perceptions and self-confidence of nurses in implementing family presence during resuscitation of adults (Powers, 2014). In another investigation, an online course incorporating asynchronous discussions with peers and a facilitator over a scheduled delivery (Curran et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…The results of the present study indicated that the personnel members who had received advanced cardiopulmonary resuscitation training had higher levels of self-con dence and more positive attitudes towards FPDR. In this regard, the results of the previous studies have shown that the personnel members' training results in an increase in their self-con dence to perform resuscitation and improves their attitudes towards FPDR [30,40,41]. In addition, based on the results, the personnel with considerable experience had higher levels of self-con dence.…”
Section: Discussionmentioning
confidence: 93%